Effects of early umbilical cord clamping versus delayed clamping on maternal and neonatal outcomes: a Jordanian study. (17th January 2021) - Mohammad, Khitam; Tailakh, Suha; Fram, Kamil; Creedy, Debra
Abstract: Objective: To compare the effects of early versus delayed cord clamping of term births on maternal and neonatal outcomes. Method: A quasi-experimental study was conducted at the Jordan University Hospital in Amman. One hundred twenty-eight mothers expecting a full-term singleton baby were assigned to delayed cord clamping (90 seconds) or early cord clamping (<30 seconds). Results: Delayed cord clamping was associated with higher hemoglobin levels among newborns after 12 hours. On the other hand, early cord clamping was associated with an increased need for oxygen therapy among newborns and occurrence of postpartum hemorrhage among mothers. There were no differences between the groups on any other variable (Apgar score at 1 and 5 minutes, admission to NICU, baby bilirubin levels after 12 hours and day 3 of birth, and mothers' Hb levels after 12 hours of childbirth). Conclusion: Term babies receiving delayed cord clamping had improved hemoglobin levels with no adverse effect on other maternal and neonatal variables. Creating evidence-based practice guidelines for umbilical cord clamping in Jordanian hospitals is essential to improve neonatal and maternal health.